Analisis Kemampuan Pemecahan Masalah dan Kemampuan Komunikasi Matematis Siswa Kelas X SMAN 2 Selong pada Materi Sistem Persamaan Linear Tiga Variabel Tahun Pelajaran 2020/2021 - Jevi Wardani; Nurul Hikmah; Tabita Wahyu Triutami; Harry Soepriyanto (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the problem-solving ability and mathematical communication skills of class X students of SMAN 2 Selong on the material of a three-variable system of linear equations in the 2021/2022 school year. This research is descriptive qualitative research. The subjects of this study were 33 students of class X-A of SMAN 2 Selong. Based on the results of the test, students who had a high score of 2 people, a medium score of 2 people, and a low score of 2 people were taken to be interviewed further. The results of this study concluded that: 1) students in high category 1 had high problem-solving and communication skills; 2) high category 2 students have high problem-solving skills and moderate communication skills; 3) moderate category 1 students have high problem-solving skills and low communication skills; 4) moderate category 2 students have moderate problem solving and communication skills; 5) low category 1 students have low problem solving and communication skills; and 6) low category 2 students have low problem solving and communication skills.